An investigation into the feasibility of using a participatory research approach in determining the information needs of a group of Coloured women in Eersterust - Snyman, M.E. (Martha Elizabeth) (University of Pretoria, 2013)
Dissertation (MIS (Information Science))--University of Pretoria, 2007.